2009
DOI: 10.1159/000217742
|View full text |Cite
|
Sign up to set email alerts
|

Visual Assessment of Left Ventricular Dyssynchrony Using Tissue Synchronization Imaging

Abstract: Background: Tissue synchronizing imaging (TSI) allows visual detection of asynchronous myocardial contraction. Although it is a screening tool for the detection of left ventricular (LV) dyssynchrony, its use as a qualitative method to assess dyssynchrony has not been studied. We evaluated the correlation of the visual assessment of dyssynchrony using TSI with quantitative assessment, the value of visual assessment to predict reverse remodeling to cardiac resynchronization therapy (CRT). Methods: Echocardiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our study showed that TD-TDI in the high septal pacing group was significantly shorter than in the apical pacing group. Measurement of regional longitudinal myocardial electrical-mechanical events at the base of the heart using velocity data acquired with TDI has been proposed to enhance identification of mechanical dyssynchrony [7,15,18]. 2D-STE may be a superior approach, because TDI is particularly affected by translational and tethering effects, and angle-dependency [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that TD-TDI in the high septal pacing group was significantly shorter than in the apical pacing group. Measurement of regional longitudinal myocardial electrical-mechanical events at the base of the heart using velocity data acquired with TDI has been proposed to enhance identification of mechanical dyssynchrony [7,15,18]. 2D-STE may be a superior approach, because TDI is particularly affected by translational and tethering effects, and angle-dependency [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used TSI method which has been used previously for assessing ventricular synchronization with relatively good level of sensitivity and specificity. 22,35 There are some plausible mechanisms such as myocardial fibrosis, chronic inflammation, or cardiomyopathy that might underline the development of ventricular asynchrony in AS. [3][4][5]36 The myocardial fibrosis may impair the myocardial electrical coupling 9 and lead to asynchronous contractions.…”
Section: Discussionmentioning
confidence: 99%
“…There are different echocardiographic techniques available for the assessment of LV asynchrony such as TDI, TSI, and strain imaging. In the present study, we used TSI method which has been used previously for assessing ventricular synchronization with relatively good level of sensitivity and specificity 22,35 …”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, a variety of echocardiographic methods have been studied, including M-mode, two-dimensional, spectral Doppler, tissue color Doppler imaging, three-dimensional echocardiography, strain and vector velocity imaging [7,8] . However, two recent randomized clinical trials did not demonstrate that mechanical dyssynchrony assessed by echocardiography is a reliable predictor of CRT responders [9,10] .In a recent issue of Cardiology , Biner et al [11] reports visual assessment of LV mechanical dyssynchrony in 86 patients including 43 patients receiving CRT. All the patients had wide QRS ( 1 120 ms), and more than half of the patients' QRS durations were more than 150 ms.…”
mentioning
confidence: 99%